Significant response to toripalimab plus axitinib for metastatic chromophobe renal cell carcinoma with sarcomatoid differentiation: a case report and literature review - Chen, Xin; Tang, Gonglin; Sun, Weicheng; Liu, Chengyue; Zhao, JunDong; Zhao, Hongwei (Frontiers in Oncology, 2025)
Chromophobe renal cell carcinoma (chRCC) is a rare subtype of renal cell carcinoma (RCC). Sarcomatoid differentiation is considered a result of dedifferentiation of the primary tumor. The coexistence of both components (chromophobe and sarcomatoid) in a single renal tumor has been infrequently reported. Currently, only isolated cases of metastatic sarcomatoid chRCC treated with immune checkpoint inhibitors (ICIs) or targeted therapies have been documented. Here, we present the first case of metastatic sarcomatoid chRCC treated with toripalimab plus axitinib and provide a review of the relevant literature. During a routine physical examination, a 58-year-old male was found to have a left renal mass. Subsequent imaging with computed tomography urography (CTU) revealed a 3.4 × 2.3 cm hypovascular tumor located in the middle pole of the left kidney, which was clinically diagnosed as left renal cell carcinoma. The patient underwent robotic-assisted laparoscopic left radical nephrectomy, and histological analysis confirmed the presence of chromophobe renal cell carcinoma with sarcomatoid differentiation. Unfortunately, twelve months post-surgery, the patient was diagnosed with retroperitoneal lymph node metastasis. Treatment with toripalimab (3mg/kg, every 2weeks) plus axitinib (5 mg orally twice daily with a 12-hour interval) was initiated, and a significant response was observed after eight months. The treatment was well tolerated, with no significant adverse reactions, and the patient is currently continuing the treatment. Metastatic chromophobe renal cell carcinoma with sarcomatoid differentiation is an extremely rare occurrence. The combination of toripalimab and axitinib may represent a promising treatment option for patients with chRCC and sarcomatoid differentiation.